Essentials of biochemistry - Fromm, Herbert; Hargrove, Mark (New York : Springer, 2012)
This textbook, Essentials of Biochemistry is aimed at chemistry and biochemistry undergraduate students and first year biochemistry graduate students. It incorporates the lectures of the authors given to students with a strong chemistry background. An emphasis is placed on metabolism and reaction mechanisms and how they are studied. As the title of the book implies, the text lays the basis for an understanding of the fundamentals of biochemistry.
References 351-352p.; Index 353-364p.
Keywords: Enzyme kinetics; Photosynthesis; Nucleotide metabolism